Budaya Literasi dan Infiltrasi Gerakan Islam Radikal di Pesantren Indonesia - Abdul Malik; Tamjidillah Tamjidillah; Satriawan Satriawan (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
Since 2002, the discourse of pesantren has been linked to radicalism. This has led to a new typology of pesantren, namely radical pesantren. This typology of pesantren is usually known to adhere to the Salafi Jihadi ideology. This article examines how Salafi Jihadi pesantrens have radical tendencies. The study mainly focused on the literacy culture that was developed. By using the qualitative-phenomenological method, this article finds that several basic concepts in Islam, in this case, the enforcement of Islamic law and the concept of jihad, have been interpreted in a pejorative way by the Salafi Jihadi pesantren community, thus causing radical and counterproductive understanding and actions to religious values. The Salafi Jihadi pesantren is different from other pesantrens that have been known before. The Salafi Jihadi pesantren teaches not only material on the fiqh of ablution, prayer, or muamalah, but also on jihad and aḥkām al-dimmah (the law of shedding blood). In addition, it was also found that culture of literacy is apparently not the only factor that determines whether a pesantren can be labelled radical or not, but there are still many other supporting factors, such as the entry of ex-radicals to pesantren, lack of government control, exclusivity, and doctrinal pedagogy.